Gait training with real-time augmented toe-ground clearance information decreases tripping risk in older adults and a person with chronic stroke - Begg, Rezaul K.; Tirosh, Oren; Said, Catherine M.; Sparrow, W. A.; Steinberg, Nili; Levinger, Pazit; Galea, Mary P. (Frontiers in Human Neuroscience, 2014)
Falls risk increases with ageing but is substantially higher in people with stroke. Tripping-related balance loss is the primary cause of falls, and Minimum Toe Clearance (MTC) during walking is closely linked to tripping risk. The aim of this study was to determine whether real-time augmented information of toe-ground clearance at MTC can increase toe clearance, and reduce tripping risk. Nine healthy older adults (76±9 years) and one 71 year old female stroke patient participated. Vertical toe displacement was displayed in real-time such that participants could adjust their toe clearance during treadmill walking. Participants undertook a session of unconstrained walking (no-feedback baseline) and, in a subsequent Feedback condition, were asked to modify their swing phase trajectory to match a “target” increased MTC. Tripping probability (PT) pre- and post-training was calculated by modelling MTC distributions. Older adults showed significantly higher mean MTC for the post-training retention session (27.7 ±3.79mm) compared to the normal walking trial (14.1± 8.3 mm). The PT on a 1cm obstacle for the older adults reduced from 1 in 578 strides to 1 in 105,988 strides. With gait training the stroke patient increased MTC and reduced variability (baseline 16±12 mm, post-training 24±8 mm) which reduced obstacle contact probability from 1 in 3 strides in baseline to 1 in 161 strides post-training. The findings confirm that concurrent visual feedback of a lower limb kinematic gait parameter is effective in changing foot trajectory control and reducing tripping probability in older adults. There is potential for further investigation of augmented feedback training across a range of gait-impaired populations, such as stroke.